Monitoring and evaluating disaster risk management capacity. Issue 3 (6th June 2016) - Scott, Zoe; Wooster, Kelly; Few, Roger; Thomson, Anne; Tarazona, Marcela
Abstract : Purpose: – The purpose of this paper is to focus on improving the monitoring and evaluation of DRM capacity development initiatives. Design/methodology/approach: – The paper first explores the complexities and challenges presented in the literature, before using empirical data from a research project in six countries (Ethiopia, Pakistan, Myanmar, Philippines, Haiti and Mozambique) to discuss current approaches to M & E of DRM capacity strengthening interventions. Findings: – This is generally an area of technical weakness in the initiatives studied, with poor understanding of terminology, little attention to outcomes or impact and few independent evaluations. The need for greater inclusion of participants in M & E processes is identified and one programme from the fieldwork in Mozambique is presented as a case study example. Originality/value: – The paper ends by presenting a unique M & E framework developed for use by DRM programmes to track the outcomes of their interventions and ultimately raise standards in this area.